HRD audit : rejuvenating HR function for business excellence - Venkateswara Rao, T. (Routledge, Taylor & Francis Group, 2025)
This book presents the first ever comprehensive approach to evaluating and redesigning Human Resource Development (HRD) function and intervention to maximise their contribution to business excellence. The HRD function recognises the significance of competent and committed people in helping organizations achieve excellence. Studies across the globe have indicated that good HR systems and practices go a long way to make firms effective. Competent employees, top management, HR staff and the HRD climate play a critical role. This book examines how users of HRD are partners in any review and evaluation. It uses multiple methods like interviews with stakeholders, observation, questionnaires, analysis of documents and workshops. The book also outlines key HRD audit methodologies to review and rejuvenate HRD and align it with business excellence including intellectual capital building for the long term. An incisive and invigorating read, this book would be useful to the students, researchers, line managers, CEOs, CXOs and faculty of Human Resource Management, Organizational Behaviour and Applied Psychology. It would also be an invaluable handbook for practising business executives to help them implement the performance management and other talent management systems for leading excellence.
Keywords: Employees -- Rating of -- India.; Executives -- Rating of -- India.; Organizational effectiveness -- Auditing.; Human capital -- India.; Personnel management -- India.; elektronické knihy; electronic books